A New Polyunsaturated Brominated Fatty Acid from a Haliclona Sponge - Aratake, Satoe (Molecular Diversity Preservation International, 2009)
A new polyunsaturated brominated fatty acid possessing acetylenic bonds 1 was isolated from the Indonesian sponge Haliclona sp. The structure of compound 1 was elucidated by analyzing its spectral data. It showed moderate cytotoxicity against cultured cells.